Placental Viral Infection Sensitizes to Endotoxin-Induced Pre-Term Labor: A Double Hit Hypothesis - Cardenas, Ingrid (2010)
PROBLEM: Among pregnant women, acquired viral infections with a concurrent bacterial infection is a detrimental factor associated to poor prognosis. We evaluate the effect of a viral infection that does not lead to pre-term labor on the response to low doses of lipopolysaccharide (LPS). Our objectives were (i) to characterize the effect of a viral infection concurrent with exposure to microbial products on pregnancy outcome and (ii) to characterize the placental and fetal immune responses to the viral sensitization to LPS. METHOD: C57B/6 wild-type mice were injected with murine gammaherpesvirus 68 (MHV68) at E8.5. Either PBS or LPS was injected i.p. at E15.5. Pregnancy outcome and cytokine / chemokine profile from implantation sites were analyzed by multiplex. RESULTS: LPS treatment of MHV-68-infected animals induced pre-term delivery and fetal death in 100% of the mice. Pre-term labor was characterized by a upregulation of pro-inflammatory cytokines and chemokines in both placenta and decidua. Similar profiles were observed from MHV-68-infected human primary trophoblast and trophoblast cell lines in response to LPS. CONCLUSION: We describe for the first time that a sub-clinical viral infection in pregnant mice might sensitize to a bacterial infection leading to pre-term delivery. We propose the ‘Double Hit Hypothesis’ where the presence of a viral infection enhances the effect of bacterial products during pregnancy leading not only to pre-term labor but likely larger adverse outcomes.